2004
DOI: 10.1021/ic040030t
|View full text |Cite
|
Sign up to set email alerts
|

Photolabile Ruthenium Nitrosyls with Planar Dicarboxamide Tetradentate N4 Ligands:  Effects of In-Plane and Axial Ligand Strength on NO Release

Abstract: Four ruthenium nitrosyls, namely [(bpb)Ru(NO)(Cl)] (1), [(Me(2)bpb)Ru(NO)(Cl)] (2), [(Me(2)bpb)Ru(NO)(py)](BF(4)) (3), and [(Me(2)bqb)Ru(NO)(Cl)] (4) (H(2)bpb = 1,2-bis(pyridine-2-carboxamido)benzene, H(2)Me(2)bpb = 1,2-bis(pyridine-2-carboxamido)-4,5-dimethylbenzene, H(2)Me(2)bqb = 1,2-bis(quinaldine-2-carboxamido)-4,5-dimethylbenzene; H is the dissociable amide proton), have been synthesized and characterized by spectroscopy and X-ray diffraction analysis. All four complexes exhibit nu(NO) in the range 1830-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 27 publications
9
139
0
Order By: Relevance
“…Having more carboxamide groups resulted in a higher bathochromic effect, higher quantum yields, and a better stability under physiological conditions [90,107,108]. An example is the tetradentate anionic ligand bpb -containing two carboxamide groups (H 2 bpb = 1,2-bis(pyridine-2-carboxamido)benzene) from which they prepared the ruthenium complexes Ru(bpb)(NO)(X) Interestingly, the more sterically crowded Ru((OMe) 2 bQb)(NO)(Cl) (Figure 11) is less photoactive than the isoquinoline analog Ru((OMe) 2 IQ1)(NO)(Cl) [32] …”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…Having more carboxamide groups resulted in a higher bathochromic effect, higher quantum yields, and a better stability under physiological conditions [90,107,108]. An example is the tetradentate anionic ligand bpb -containing two carboxamide groups (H 2 bpb = 1,2-bis(pyridine-2-carboxamido)benzene) from which they prepared the ruthenium complexes Ru(bpb)(NO)(X) Interestingly, the more sterically crowded Ru((OMe) 2 bQb)(NO)(Cl) (Figure 11) is less photoactive than the isoquinoline analog Ru((OMe) 2 IQ1)(NO)(Cl) [32] …”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…The nitrite to NO conversion can be effected by either a heme or copper enzyme (vide infra) and the NO to N 2 O transformation also involves hemes (see below). Further, relevant syn- thetic/chemical research includes the study of the catalytic reduction of NO (or other nitrogen oxides) (mentioned below) and as mentioned above the development of (metallo) reagents as drugs designed to thermally or photochemically release NO [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Heme Proteins: Guanylate Cyclase -mentioning
confidence: 99%
“…The use of metal ion chemistry for such purposes is a very active area of research, i.e. to sense biological NO [23][24][25][26][27], deliver it as drug [28][29][30][31][32][33][34][35][36][37][38] or modulate NO concentrations (as in septic shock therapy [39,40]). Another form of cellular signaling is thought to also involve NO, but with biological thiols [41], consisting of nitrosylation-denitrosylation chemistry, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium nitrosyls are particularly attractive in this regard owing to their thermal stability and NO release upon exposure to light. [7][8][9] The NO release, in most of the octahedral ruthenium nitrosyls having {Ru II NO + } moiety, can be induced by one electron reduction by photolysis or PDT. In general, it has been found that NO release depends markedly on the p-acceptor strength of the ligand coordinated trans to NO and increase in plane ligand field strength.…”
Section: Introductionmentioning
confidence: 99%